Gut Dysfunction and Non-alcoholic Fatty Liver Disease - Grabherr, Felix; Grander, Christoph; Effenberger, Maria; Adolph, Timon Erik; Tilg, Herbert (Frontiers in Endocrinology, 2019)
Non-alcoholic fatty liver disease (NAFLD) has emerged as one of the leading liver diseases worldwide. NAFLD is characterised by hepatic steatosis and may progress to an inflammatory condition termed non-alcoholic steatohepatitis, (NASH), liver cirrhosis and hepatocellular carcinoma. It became evident in the last years that NAFLD pathophysiology is complex and involves diverse immunological and metabolic pathways. An association between intestinal signals (e.g. derived from the gut microbiota) and the development of obesity and its metabolic consequences such as NAFLD are increasingly recognized. Preclinical studies have shown that germ-free mice are protected against obesity and hepatic steatosis. Several human studies from the past years have demonstrated that NAFLD contains a disease-specific gut microbiome signature. Controlled studies propose that certain bacteria with rather pro-inflammatory features such as Proteobacteria or Escherichia coli are dominantly present in these patients. In contrast, rather protective bacteria such as Faecalibacterium prausnitzii are decreased in NAFLD patients. Furthermore, various bacterial metabolites and microbiota-generated secondary bile acids are involved in NAFLD-associated metabolic dysfunction. Although these findings are exciting, research currently lack evidence that interference at the level of the gut microbiome is beneficial for these diseases. Further preclinical and clinical studies are needed to advance this aspect of NAFLD research and to support the notion that the intestinal microbiota is indeed of major relevance in this disorder.